Influence of Price Cuts and Product Quality on Interest to Buy: Case Study: Yotta Indonesia - Rahmat Riwayat Abadi; Andi Dewi Angreyan (International Humanity Advance, Business & Sciences, 2023)
UMKM Yotta Indonesia is one of the businesses located in Makassar City which has a role in selling in its environment. In this study, three variables were used, namely price discounts (X1), product quality (X2) and purchase intention (Y). This study aims (1) to determine the effect of price discounts on purchase intention (2) to determine the effect of product quality on purchase intention. This type of research is a quantitative research that is descriptive in nature, which aims to describe the effect of each variable. The sample in this study were 50 respondents and this study used accidental sampling. The results of this study indicate that price discounts and product quality have a positive and significant effect on purchase intention.